A study on educational needs of adults (on the example of Zaporizhzhia region residents) - Прийма, Сергій Миколайович; Прийма, Сергей Николаевич; Pryima, Serhii; Orlov, A.; Anishchenko, O.; Pozdnyakova-Kirbyateva, E. (My University, 2018)
Lifelong learning is a determining factor of the city's or region's successful socio-economic development, the development of its human potential, the basis for the regional education policy. The theoretical substantiation, development and experimental verification of the conceptual grounds of the regional education policy require a careful analysis of both the educational capacity of the region and the study of the educational needs of the region residents, which confirms the urgency of the integrated monitoring of citizens' educational needs and the level of their satisfaction. In order to identify the educational needs of Zaporizhzhia region residents and the level of their satisfaction, 400 respondents have been surveyed. The survey was conducted in the form of a standardised interview with the ―face-to-face‖ method according to the respondents' residence using a specially designed tool (a questionnaire) which included 20 principal questions and 9 questions of socio-demographic character. The structure of the interview was developed in accordance with the specific features of the research topic and it was divided into conventional blocks, including identification of the current state of the education services market in the region and assessment of its strengths and weaknesses, analysis of the structure of the education services market in the region, studying the educational demands and needs of the region residents, and mapping the potential possibilities for the development of the education services market. According to the results of the study, it was concluded that 57.5% of Zaporizhzhia region residents are in need of educational services. The most important reasons indicated by the respondents is the acquisition of the knowledge necessary for achieving success in the profession (46.7%), the opportunity to get a diploma, licence or certificate (30.1%), the opportunity to increase chances in the labour market (19.2%). The inhabitants of the region mostly get information from the Internet (62.0%). The analysis of the survey results revealed the trends (the understanding how important the role of education throughout life is, the priority of educational activities regardless of age, the level and profile of previous education, the nature of employment, work experience, income or residence area of respondents, the increase in interest in getting educational services among the rural population of the region, the need to create conditions for the updating of knowledge and retraining, which is related to increasing competition in the labour market, the increase in demand for active and practically directed teaching methods) and the factors (accessibility and interconnection of different levels and forms of education, the need for constant dialogue and use of feedback mechanisms in the development and implementation of regional programmes and development strategies, the need to create experimental pilot projects as promising resource centres on management of regional education development) influencing education development in the region. The results of the study of the educational needs of the region residents can be used in order to identify the priority areas of the regional education policy.
Keywords: lifelong learning; adult education; learning city/learning region; educational needs; education services market